2007
DOI: 10.1007/s10705-007-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

Yield and soil nutrient balance of a sugarcane plant–ratoon system with conventional and organic nutrient management in sub-tropical India

Abstract: A 3-year field trial of sugarcane, comprising 11 treatment combinations of different organic manures with and without Gluconacetobacter diazotrophicus (Gd), NPK and an absolute control, on an inceptisol was conducted to assess the effect of these treatments on sugarcane total and economic yield, the benefit:cost ratio, nutrient balance and soil quality in a sugarcane plant-ratoon system. The highest cane yield (78.6 t ha À1 ) was recorded in the plant crop given vermicompost + Gd, whereas ratoon yields (first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
4
13
0
8
Order By: Relevance
“…Higher economic returns (Rs 326393/ha) with B: C (3.60) ratio was obtained at higher N doses because higher nitrogen levels increased the number of millable canes, fresh weights, dry matter contents, cane yields and stover yields. These results are in conformity with the findings of Singh et al (2007). The study also demonstrated that the profitability of net monetary returns (Rs 265707/ha) was fetched from 20 cm height of earthed up as compared to 10 cm earthed up crop during both the ratoon crops of sugarcane.…”
Section: Nutrient Uptake By Sugarcane Plantsupporting
confidence: 90%
“…Higher economic returns (Rs 326393/ha) with B: C (3.60) ratio was obtained at higher N doses because higher nitrogen levels increased the number of millable canes, fresh weights, dry matter contents, cane yields and stover yields. These results are in conformity with the findings of Singh et al (2007). The study also demonstrated that the profitability of net monetary returns (Rs 265707/ha) was fetched from 20 cm height of earthed up as compared to 10 cm earthed up crop during both the ratoon crops of sugarcane.…”
Section: Nutrient Uptake By Sugarcane Plantsupporting
confidence: 90%
“…Produtividade de colmos, acúmulo de matéria seca e N total da parte aérea de cana de açúcar, das safras 2006/2007 e 2008/2009, com adubação nitrogenada, inoculação de bactérias diazotróficas e controle sem inoculação (1) . Além disso, o maior vigor, confirmado pelo aumento na produtividade, no acúmulo de matéria seca e N total na parte aérea das plantas com inoculação, observado na variedade RB867515, também poderia estar associado a outros efeitos promotores de crescimento, além da FBN, como produção de fitormônios (Fuentes-Ramírez et al, 1993;Suman et al, 2001;Bashan et al, 2004), solubilização de fosfatos (Singh et al, 2007;Shukla et al, 2008), aumento no teor de C orgânico do solo, aumento de N e retenção de nutrientes essenciais na rizosfera (Yadav et al, 2009).…”
Section: Resultsunclassified
“…Há muitas evidências de que a cana-de-açúcar seja beneficiada pela interação com bactérias diazotróficas (Boddey et al, 2003). As formas pelas quais a associação pode beneficiar o desenvolvimento e a produtividade das plantas são: a fixação biológica de nitrogênio (FBN) (Urquiaga et al, 1992); a produção de hormônios promotores de crescimento, como o ácido indolacético (Suman et al, 2001); a solubilização de fosfatos, (Singh et al, 2007;Shukla et al, 2008); o aumento no teor de carbono orgânico do solo; e o aumento de N e retenção de nutrientes essenciais na rizosfera (Yadav et al, 2009).…”
Section: Introductionunclassified
“…Maximum decrease in soil bulk density (12%) with an increase in soil aggregate (17%) and water infiltration rate (35%) was obtained with the addition of sulphitation press mud cake (Singh et al 2007).…”
Section: Pressmudmentioning
confidence: 98%